2017
DOI: 10.1002/jts.22154
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Memories in Women Abused by Their Intimate Partner: Analysis of Traumatic and Nontraumatic Narratives

Abstract: Traditional models of posttraumatic stress disorder (PTSD) claim that the high emotional intensity of traumatic events leads to deficits in the voluntary access of traumatic memories. This may result in disorganized narratives, with a high sense of emotional and sensory reliving. Alternatively, the basic mechanisms view suggests that high arousal leads to more available involuntary and voluntary memories. Traumatic narratives would not be impaired; indeed, they would be immersive and rich in detail. To test th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 27 publications
0
13
1
Order By: Relevance
“…These findings mirror results reported in a previous study in which increased use of “we” words was correlated with fewer acute PTSD symptoms, including hyperarousal symptoms, in individuals experiencing traumatic symptoms related to the September 11, 2001, terrorist attacks (D'Andrea et al., ). Our results are inconsistent with what was reported in one study in which the authors found that first‐person pronoun use was a significant predictor of the severity of self‐reported hyperarousal symptoms in women exposed to interpersonal violence (Fernández‐Lansac & Crespo, ). One potential explanation for this discrepancy is related to differences between studies in terms of participant samples.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…These findings mirror results reported in a previous study in which increased use of “we” words was correlated with fewer acute PTSD symptoms, including hyperarousal symptoms, in individuals experiencing traumatic symptoms related to the September 11, 2001, terrorist attacks (D'Andrea et al., ). Our results are inconsistent with what was reported in one study in which the authors found that first‐person pronoun use was a significant predictor of the severity of self‐reported hyperarousal symptoms in women exposed to interpersonal violence (Fernández‐Lansac & Crespo, ). One potential explanation for this discrepancy is related to differences between studies in terms of participant samples.…”
Section: Discussioncontrasting
confidence: 99%
“…One potential explanation for this discrepancy is related to differences between studies in terms of participant samples. The study by Fernández‐Lansac and Crespo () included trauma‐exposed women regardless of whether they met criteria for PTSD whereas our study included only women who met clinical criteria for PTSD. Another possible reason for this inconsistency between studies could be related to differences in depressive symptoms, which have been reliably shown to be associated with more self‐focus (e.g., Ingram et al., ; Ingram & Smith, ; Philippi et al., ); these were not controlled for in the previous study.…”
Section: Discussionmentioning
confidence: 99%
“…Rape victims often describe their memories as emotionally intense but lacking coherence ( 53 ), whereas other victims report memories rich in detail. A recent study asked survivors of domestic violence to write a narrative about a traumatic event and a positive experience ( 54 ). The trauma narratives were detailed and more coherent than the memories of a positive experience, and were better predictors of PTSD.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Peace and Porter (2004) have shown that traumatic events are remembered better than non-traumatic events 3 months after they occur Peace et al (2008) found, by comparing memories of sexual assault and non-traumatic events, that the former were more vivid, detailed and sensory than the latter. Fernández-Lansac and Crespo (2017) found that memories of traumatic experiences in abused battered women were more detailed and spatially oriented than positive memories.…”
Section: Introductionmentioning
confidence: 95%